Returns to university higher education in Peru: The Effect of Graduation - Salazar Condor, Víctor Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study measures the importance of finalizing university higher education in the income of Peruvian workers. Thus, information from the National Household Survey of Peru is analyzed, estimating three regression models based on who finished university studies and who did not. Our results show that completing university presents higher private returns than not doing it, and that the gap in returns by sex is shortened in those who finish their studies. In addition, there are higher returns in urban areas, capital cities, quality universities, and in those who do not study an education career.